Peran Strategis Elit Lokal dan Konsep Pengembangan Desa Wisata di Kabupaten Pandeglang - Neka Fitriyah; Anna Gustina Zainal; Sarwititi Sarwoprasodjo (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Pandeglang Regency is home to numerous potential tourism villages dispersed across various locations; however, their management remains fragmented and lacks comprehensive stakeholder involvement. This study examines the participation and role of local elites in tourism village development through a qualitative approach involving in-depth interviews and observations. The findings reveal that Community-Based Tourism (CBT), emphasizing community participation in organizing, managing, and developing tourism independently with self-awareness, is the most suitable concept for the region. Local elite participation manifests in two forms: mechanical participation, driven by external systemic requirements, and organic participation, arising from the elites’ intrinsic awareness and commitment. The political roles of local elites are categorized as opinion leaders generating and disseminating ideas, mediators bridging aspirations and interests among stakeholders, and decision-makers formulating and implementing policy decisions. It is recommended that tourism village development actively involves local elites to ensure shared responsibility and accountability in addressing potential challenges.